The Effect of n-3 Polyunsaturated Fatty Acid Supplementation on Androgen Status in Patients with Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis of Clinical Trials - Hajishafiee, M.; Askari, G.; Iranj, B.; Ghiasvand, R.; Bellissimo, N.; Totosy de Zepetnek, J.; Salehi-Abargouei, A. (Hormone and Metabolic Research, 2016)
The anti-androgenic role of n-3 polyunsaturated fatty acids (PUFAs) among patients with polycystic ovary syndrome (PCOS) has recently been proposed. The present study aimed to systematically review clinical trials assessing the effects of n-3 PUFAs consumption on androgen status among adult females with PCOS. PubMed, ISI Web of Science, Google Scholar, and Scopus were searched up to December 2015. Clinical investigations assessing the effect of n-3 PUFAs on adult females with PCOS were included. Mean±standard deviation of change in serum total testosterone, sex hormone binding globulin (SHBG), and dehydroepiandrostrone sulfate (DHEAS) were extracted. Eight clinical trials with 298 participants were eligible. Meta-analysis showed that n-3 PUFAs supplementation marginally reduces total testosterone (mean difference [MD]: − 0.19 nmol/l; 95% CI: − 0.39 to 0.00; p=0.054), but not SHBG (MD: 1.75 nmol/l; 95% CI: −0.51 to 4.01; p=0.129) or serum DHEAS levels (Hedes’ g: −0.11 nmol/l; 95% CI: −0.29 to 0.06; p=0.19) among adult females with PCOS. Subgroup analyses showed that only before-after studies (Hedges’ g: 0.15; 95% CI: −0.27 to −0.04; p=0.01) and long-term interventions (>6 weeks) (Hedges’ g: −0.17; 95% CI, −0.29 to −0.05; p=0.004) had reducing effects on serum DHEAS levels. The majority of long-term trials utilized a single group design (no control group). It does not appear that n-3 PUFAs supplementation significantly affects the androgenic profile of females with PCOS; however, some before-after and long-term intervention studies show reduced DHEAS levels. Future studies incorporating double blinded placebo controlled clinical trials with long follow-up periods are warranted.
Keywords: n-3 polyunsaturated fatty acids; polycystic ovary syndrome; systematic review; meta-analysis